A Star (A*) Algorithm Implementation to Measure Shortest Distance from Universitas Negeri Medan to Kualanamu International Airport - Dedy Kiswanto (Universitas Pendidikan Indonesia (UPI), 2023)
Searching for the shortest path is a problem that often occurs in everyday life, to determine the best distance some information is needed such as the value / cost between points to be visited. The A* (A Star) algorithm is one of the optimal algorithms in the shortest path search category. This algorithm is very good as a solution to the pathfinding process so that it can save time and money. This research was conducted to determine the shortest distance from Medan State University to Kualanamu International Airport using the A* (A Star) algorithm. The method used in this study is by collecting data using Google Maps, building a graph model as a map representation, calculating the shortest distance and evaluating it. The research results obtained show the accuracy of the A* algorithm in determining the shortest route from Medan State University to Kualanamu Airport where this can save time and money on the way.